The Social Control and Technology ? the Control of Technology. The Case of Sport - Nosal, Przemysław (INSTED: Interdisciplinary Studies in Education & Society, 2015)
The paper concerns the relations between social control and technology. This phenomenon is illustrated by examples from a sport field. The sport remains a great indicator of social and technological changes, so it serves as an useful research context. The text analyses the three occurrences from nowadays sport world: legless athlete Oscar Pistorius and his artificial limbs; ?shark skin? swimsuits; Frank Lampard?s disallowed goal in World Cup 2010. The cases lead to the two main questions. The first one is as follows: who (should) control technology in sport? The second one ? how the technology should be controlled? The basis of this paper is an empirical research. The survey was conducted in sport environment. It uses the case study method. Within the method three minor technics were used: desk research, discourse analysis and expert?s IDI.